Three-Dimensional Finite Element Analysis of Vertical and Angular Misfit in Implant-Supported Fixed Prostheses - Assunção, Wirley Goncalves [UNESP]; Gomes, Erica Alves [UNESP]; Rocha, Eduardo Passos [UNESP]; Delben, Juliana Aparecida [UNESP] (Quintessence Publishing Co Inc, 2011)
Purpose: Three-dimensional finite element analysis was used to evaluate the effect of vertical and angular misfit in three-piece implant-supported screw-retained fixed prostheses on the biomechanical response in the peri-implant bone, implants, and prosthetic components. Materials and Methods: Four three-dimensional models were fabricated to represent a right posterior mandibular section with one implant in the region of the second premolar (2PM) and another in the region of the second molar (2M). The implants were splinted by a three-piece implant-supported metal-ceramic prosthesis and differed according to the type of misfit, as represented by four different models: Control = prosthesis with complete fit to the implants; UAM (unilateral angular misfit) = prosthesis presenting unilateral angular misfit of 100 pm in the mesial region of the 2M; UVM (unilateral vertical misfit) = prosthesis presenting unilateral vertical misfit of 100 pm in the mesial region of the 2M; and TVM (total vertical misfit) = prosthesis presenting total vertical misfit of 100 pm in the platform of the framework in the 2M. A vertical load of 400 N was distributed and applied on 12 centric points by the software Ansys, ie, a vertical load of 150 N was applied to each molar in the prosthesis and a vertical load of 100 N was applied at the 2PM. Results: The stress values and distribution in peri-implant bone tissue were similar for all groups. The models with misfit exhibited different distribution patterns and increased stress magnitude in comparison to the control. The highest stress values in group UAM were observed in the implant body and retention screw. The groups UVM and TVM exhibited high stress values in the platform of the framework and the implant hexagon, respectively. Conclusions: The three types of misfit influenced the magnitude and distribution of stresses. The influence of misfit on peri-implant bone tissue was modest. Each type of misfit increased the stress values in different regions of the system. INT J ORAL MAXILLOFAC IMPLANTS 2011;26:788-796
Keywords: abutment stress; biomechanics; dental implant; dental prosthesis; finite element analysis; implant stress